2013
DOI: 10.1002/joc.3682
|View full text |Cite
|
Sign up to set email alerts
|

Tibetan Plateau precipitation as depicted by gauge observations, reanalyses and satellite retrievals

Abstract: The European Centre for Medium-range Weather Forecasts (ECMWF) reanalysis ERA-40, ERA-Interim, University of Washington (UW) data, APHRODITE's Water Resources (APHRODITE), and Tropical Rainfall Measuring Mission (TRMM) Multisatellite Precipitation Analysis (TMPA) precipitation estimates are compared with each other and with the corrected gauge observations over the Tibetan Plateau (TP) at both basin and plateau scales. The ERA-40 generally can capture the broad spatial and temporal distributions in the gauge-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
139
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(154 citation statements)
references
References 78 publications
(95 reference statements)
13
139
0
2
Order By: Relevance
“…The change of ET was positive in the edge area, except at the northern and southeastern edge of the Tibetan Plateau. ET increased in this region, partly due to the increase in precipitation [50,[56][57][58]. However, ET decreased in the middle part of the Tibetan Plateau, including almost all of Tibet.…”
Section: Dynamics Of Et the Spatial Distribution Of Et Overmentioning
confidence: 99%
“…The change of ET was positive in the edge area, except at the northern and southeastern edge of the Tibetan Plateau. ET increased in this region, partly due to the increase in precipitation [50,[56][57][58]. However, ET decreased in the middle part of the Tibetan Plateau, including almost all of Tibet.…”
Section: Dynamics Of Et the Spatial Distribution Of Et Overmentioning
confidence: 99%
“…The TP, known as the "third pole", has an average elevation of over 4000 m above sea level (a.s.l) [42]. The TP is also the source of many Asian rivers, such as the Yellow River, the Yangtze River, and the Mekong River, supporting hundreds of millions of people living downstream [43].…”
Section: Introductionmentioning
confidence: 99%
“…However, accurate observation of precipitation is challenging in many remote regions of the world, such as the Tibetan Plateau (TP), due to sparse gauge networks and high spatial variability in precipitation [1,2]. Satellite remote sensing has provided unprecedented precipitation information at a broader range of time and space scales, representing a significant contribution toward mapping global rainfall [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made to assess the suitability of satellite precipitation products over the TP [1,[7][8][9][10][11]. Previous studies found that the TMPA precipitation products outperform other satellite products (e.g., PERSIANN and CMORPH) across the plateau with lower errors and biases [9,11].…”
Section: Introductionmentioning
confidence: 99%